2014
DOI: 10.1097/mpg.0000000000000216
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Iron Deficiency in Healthy Young Children in the Southwestern Netherlands

Abstract: ID is present in 18.8% of healthy children ages 0.5 to 3 years and living in the southwestern region of the Netherlands. The present visit of preschool/day care and the use of formula are associated with a reduced risk of ID, whereas a high intake of cow's milk is associated with an increased risk of ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 37 publications
(79 reference statements)
4
34
3
Order By: Relevance
“…Among children aged 1 to 3 years, 13% of children who received formula were iron deficient, whereas among children not receiving formula, 30.5% were iron deficient. The intake of >400 ml of cow's milk per day occurred significantly and more frequently in children with ID than in those without ID [67]. Other studies including children conducted in Albania [53], Greece [56], Iceland [58] and the United Kingdom [62] found similar prevalence rates of ID from 27 to 48%.…”
Section: Iron Statusmentioning
confidence: 60%
See 2 more Smart Citations
“…Among children aged 1 to 3 years, 13% of children who received formula were iron deficient, whereas among children not receiving formula, 30.5% were iron deficient. The intake of >400 ml of cow's milk per day occurred significantly and more frequently in children with ID than in those without ID [67]. Other studies including children conducted in Albania [53], Greece [56], Iceland [58] and the United Kingdom [62] found similar prevalence rates of ID from 27 to 48%.…”
Section: Iron Statusmentioning
confidence: 60%
“…Twenty-two studies reported on ID prevalence estimates [24,32,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67], of which 15 studies showed results for infants (6-12 months of age) [24,32,48,49,50,51,52,55,57,59,60,61,63,64,67]. …”
Section: Iron Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Children referred for adenotomy or tonsillectomy were not included because the prevalence of upper airway infections in these children is high. Exclusion criteria were known infection in the last 4 wk, use of iron supplementation within the last 6 wk, blood transfusion within the last 6 mo, preterm birth before 32 wk gestational age (GA), known hemoglobinopathies, oncologic disorders, multiple congenital malformations and metabolic diseases as described previously (25). The study was approved by the Medical Ethics Committee of South-West Holland.…”
Section: Study Populationmentioning
confidence: 99%
“…We included 400 children aged 0.5-3 y undergoing general anesthesia because of simple elective surgery or diagnostic procedure in two different hospitals in the Southwestern region of the Netherlands between August 2011 and May 2012 (25). This was originally a crosssectional study on prevalence and risk factors of ID.…”
Section: Study Populationmentioning
confidence: 99%